2015
DOI: 10.3928/01913913-20150114-03
|View full text |Cite
|
Sign up to set email alerts
|

Cataract Surgery in Children With Uveitis: Retrospective Analysis of Intraocular Lens Implantation With Anterior Optic Capture

Abstract: The technique of cataract extraction with IOL placement and anterior prolapse of the optic through the anterior capsulorhexis shows promise to be a safe and viable option for pediatric patients with chronic uveitis treated with systemic immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Taken together, studies found that cataract surgery, regardless of IOL implantation, generally improved vision. Nearly all studies specifically highlighted the need for intensive immunosuppressive treatment and control of uveitis after cataract surgery, but it was unclear whether it was a question of sustaining preexisting regimen or based on a change in the need for controlling the uveitis [16,20,21,[32][33][34][35][36].…”
Section: Results Of Individual Studies and Risk Of Bias Within Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Taken together, studies found that cataract surgery, regardless of IOL implantation, generally improved vision. Nearly all studies specifically highlighted the need for intensive immunosuppressive treatment and control of uveitis after cataract surgery, but it was unclear whether it was a question of sustaining preexisting regimen or based on a change in the need for controlling the uveitis [16,20,21,[32][33][34][35][36].…”
Section: Results Of Individual Studies and Risk Of Bias Within Studiesmentioning
confidence: 99%
“…Nine studies provided eligible and comparable data for the meta-analyses [16,20,21,30,[32][33][34][35][36]. ese studies collectively summarized data on 256 eyes: 153 eyes underwent IOL implantation and 103 eyes were aphakic.…”
Section: Synthesis Of Results In Meta-analyses and Risk Of Bias Across Studiesmentioning
confidence: 99%
See 3 more Smart Citations